Syekh Nawawi Al-Bantani: Kontribusi Pemikiran Pendidikan Islam Dan Relevansinya Pada Era Modern - Erlina Farah Agustina (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2024)
This research explains the concept of Syekh Nawawi's Islamic educational thought and its relevance today. Sheikh Nawawi al-Bantani himself is a great scholar from Banten who is famous for his work in the field of Islamic religion. This research uses a type of library research that uses descriptive analysis with the aim of systematically describing the facts found. The results of his findings can be seen from the thoughts on Islamic education that he conveyed. His thoughts include the essence of Ta'lim, Tarbiyah and Ta'dib, then the objectives of Islamic education, sources of Islamic education, principles of Islamic education, educators and students. Apart from that, the results of this research show that Syekh Nawawi's thoughts about Islamic education are still relevant today. The objectives, values and methods can be a guide for educators and students in realizing quality Islamic education.